Faktor Risiko Transmisi Virus HIV pada Ibu Hamil di Papua - Rabrageri, Alberthzon Kris Silo; Siswosudarmo, Risanto; Soetrisno, Soetrisno (JURNAL KESEHATAN REPRODUKSI, 2017)
Background: Human Immunodeficiency Virus (HIV) has been transmitted all over the world and attack people including pregnant women and their fetus. HIV-AIDS has become the main cause of maternal death. The transmission is started from Africa to Indonesia, specifically to Papua Island. In Papua, HIV is a serious threat for pregnant women’s life because of its fast transmission, even faster from other regions in Indonesia. Until present, there has no research about HIV transmission on pregnant women in Papua Island.Objective: To conduct analysis on risk factors related to HIV transmission on pregnant women in Papua Island.Method: Cross sectional continued with retrospective cohort. Data was taken from medical record of all patients delivering in eight state-owned hospitals in Papua and West Papua provinces started from 1 January 2013 to 31 December 2013. Inclusion criteria were all pregnant women who delivered vaginally or by caesarean sections with HIV and non HIV diagnosis and had complete medical record data. Data being taken included mother’s age when delivered the baby, mother’s education, parents’ social economic status, mother’s ethnicity, parents’ domicile, prematurity and infant’s birth weight. The two research groups were HIV (+) and HIV (-) groups. Data were statistically analyzed using Pearson Chi Square for univarian and logistic regression for multivarian.Result and Discussion: In Papua island, prevalence of pregnant women with HIV was 15.3%, and mostly occurred in reproductive age ( 85.1%). The main transmission source was heterosexual (100%). Univarian analysis found that mothers’s age <20 years old when delivered the baby increase 1.12 times compared to > 20 years old but it’s statistically insignificant (p=0.53). Mothers education < 9 years increases the risk of HIV 1.4 times compared to mother’s education > 9 years (p=0.01). The husband’s low socioeconomic status increase the risk of 5.51 times compared with husband’s high socioeconomic status (p<0.01). The wife’s low socioeconomic status increase the risk of 1.22 times, in which statistically insignificant (p=0.14). Native Papuanese pregnant women has significantly 3.05 times higher risk for HIV transmission compared to non Papuanese (p<0.01). Pregnant women’s domicile in villages increase the transmission significantly 2.21 times compared to cities’ domiciles (p<0.00). Premature delivery increased HIV transmission by 1.7 times (p<0.01). Low infant body weight increased the transmission by 1.64 times significantly (p<0.01). Multivarian analysis showed that husband’s low socioeconomic status, Papuanese ethnicity and domicile in villages are the most dominant factors influencing HIV transmission on pregnant women in Papua Island.Conclusion: Varied risk factors on HIV transmission resulted in the occurrence of HIV (+) cases in Papua Island, while the most dominant factors are husband with low socioeconomic status, Papua ethnicity and domicile in villages.Keywords: HIV, risk factors, birthing mothers, Papua Island.